Reticulocyte and erythrocyte hypochromia markers in detection of iron deficiency in adolescent female athletes - Malczewska-Lenczowska, J; Orysiak, J; Szczepańska, B; Turowski, D; Burkhard-Jagodzińska, K; Gajewski, J (Biology of Sport, 2017)
The aim of this study was to analyse the effectiveness of new haematology parameters related to reticulocytes and mature red blood cells to differentiate pre latent and latent iron deficiency. The study included 219 female athletes (aged 15-20 years) representing volleyball, handball, cycling, canoeing, cross-country skiing, swimming and judo. To assess iron status the concentration of ferritin, soluble transferrin receptor (sTfR), iron and total iron binding capacity (TIBC) were determined in serum. In addition to blood morphology, the mean cellular haemoglobin content in erythrocytes (CH) and reticulocytes (CHr), mean cellular haemoglobin concentration in reticulocytes (CHCMr), the percentage of erythrocytes (HYPOm) and reticulocytes (HYPOr) with decreased cellular haemoglobin concentration, the percentage of erythrocytes (LowCHm) and reticulocytes (LowCHr) with decreased cellular haemoglobin content, and percentage of erythrocytes with decreased volume (MICROm) were determined. Subjects with ferritin <30 ng/ml were classified as having stage I (pre-latent) iron deficiency (ID). The second stage (latent ID) was diagnosed when low ferritin was accompanied by elevated sTfR and/or elevated TIBC values. The frequency of ID (without anaemia symptoms) was high, amounting to 60% (stage I in 45%, stage II in 15% of subjects). In subjects with stage I ID significant changes in haematological variables concerned mainly reticulocytes: CHCMr (p<.001), CHr (p<.05), LowCHr (p<.05), HYPOr (p<.001) in comparison to normal iron stores. In athletes with latent ID, there were also significant changes (p<.001) in many indices of mature red blood cells, i.e. haemoglobin concentration (Hb), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), CH, %LowCHm, as well as %MICROm (p<.01) in relation to the group without iron deficiency. The main finding of this study was that the diminished or exhausted iron stores had already caused changes in reticulocytes, and intensified iron deficiency (stage II) increased changes in both reticulocytes’ and erythrocytes’ hypochromia indices, while microcythaemia symptoms appeared later. This suggests that the markers of hypochromia relating especially to reticulocytes are useful for diagnosis of early ID in athletes with absence of an acute phase reaction.